2020
DOI: 10.1002/aoc.6068
|View full text |Cite
|
Sign up to set email alerts
|

Two dinuclear copper (II) and nickel (II) complexes based on 4‐(diethylamino)salicylaldehyde: X‐ray structures, spectroscopic, electrochemical, antibacterial, Hirshfeld surfaces analyses, and time‐dependent density functional theory calculations

Abstract: The quinazoline-type ligand 2-(4-diethylamino-2-hydroxyphenyl)-4-methyl-1,-2-dihydroquinazoline 3-oxide (HL 1 ; H is the deprotonatable hydrogen) was prepared. Two 2-D supramolecular complexes [Cu 2 (L 2) 2 (NO 3) 2 ] (1) and [Ni 2 (L 2) 2 (CH 3 COO) 2 ] (2) (L 2 = 1-(2-{[(E)-(4-diethylamino-2-hydroxybenzylidene] amino} phenyl)ethanone oxime) were synthesized using HL 1 and characterized by elemental analysis, spectroscopic methods, and single-crystal X-ray diffraction studies. It revealed that 1 had coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 89 publications
2
7
0
Order By: Relevance
“…The ESP map described the stability of the electrostatic properties of complexes, which played an important role in predicting the structure. [65,66] These theories were in accordance with the experimental results of X-ray crystallography. Therefore, the electrophilic and nucleophilic attack sites were measured by ESP calculations.…”
Section: Charge Distribution and Espsupporting
confidence: 86%
“…The ESP map described the stability of the electrostatic properties of complexes, which played an important role in predicting the structure. [65,66] These theories were in accordance with the experimental results of X-ray crystallography. Therefore, the electrophilic and nucleophilic attack sites were measured by ESP calculations.…”
Section: Charge Distribution and Espsupporting
confidence: 86%
“…From the ESP figure, it was observed that negative regions (red spheres) were distributed over the nitrogen atom of the imidazole ring or nitrate, while the positive regions (blue spheres) were mainly localized the H-atoms. [66] These theoretical consequences were in well keeping with the experimental values of X-ray diffraction. Hence, the electrophilic and nucleophilic attack sites were determined using ESP calculations; it was verified that hydrogen bonds were aware in the optimized structure of the crystal.…”
Section: Charge Distribution and Electrostatic Potentialsupporting
confidence: 73%
“…These characteristics were in good agreement with the quasiinvertibility of similar complexes in the refences. [52] 3.5 | Electron paramagnetic resonance spectroscopy EPR spectra of samples 1 and 2 were measured at 300 K. As shown in Figure 9 (2.241 or 2.049) > g e (2.0023) indicated that the paramagnetic centers of octahedron, square plane and pyramid geometry were axisymmetric, and single unpaired electron of Cu (II) ion was located at d(x 2 À y 2 ) ground state. The g k value was regarded as a momentous parameter for the covalent properties of the metal-ligand bond.…”
Section: Electrochemistry Studiesmentioning
confidence: 98%